Petrology and Geochemistry of Early Cambrian Volcanic Rocks Hosting the Kiruna-type Iron Ore in Anomaly 10 of Sechahun, Central Iran - A. Eslamizadeh (Journal of Sciences, Islamic Republic of Iran)
Early Cambrian volcanic rocks of the Posht-e Badam tectonic block in Central Iran which is hydrothermally altered to green color rocks, hosts the Kiruna-type Iron Oxide-Apatite (IOA) mineralization in Anomaly 10 of Sechahun deposit. Geochemically, these volcanic rocks are classified as high-potassium calc-alkaline and mainly consist of rhyolite and trachyandesite. These rocks are important for hosting the REE- bearing apatite-iron oxide ores. The rhyolitic tuffs with a likely common origin are associated with the volcanic rocks. In this research, a selection of samples from Anomaly 10 of Sechahun has been studied with respect to their geochemistry and petrography with a special focus on REE-bearing phases. The bulk geochemistry of the rock units was analyzed using (ICP-OES) and (ICP-MS) methods. The ore samples were studied using ore microscopy and scanning electron microscopy with the energy-dispersive X-ray spectroscopy (SEM-EDS) techniques. The results indicated that mineralization has occurred by magmatic differentiation, forming magnetite, hematite, and apatite, followed by hydrothermal reworking, forming minerals such as hematite ± actinolite. Dendritic forms of magnetite, and apatite are common in the area. Apatite grains with monazite inclusions are generally enriched in LREE. The similar distribution of trace elements in various types of volcanic rocks in Anomaly 10 indicates a co-genetic origin and possible petrogenetic relation of these rocks. The whole rocks have been derived from differentiation of a single magmatic source. This magma with a probable melasyenitic initial composition erupted in a rifting tectonic environment and experienced some partial melting of the crust.